Unleashing Bihar's agriculture potentia: Sources and drivers of agriculture growth - Anwarul Hoda; Pallavi Rajkhowa; Ashok Gulati (Indian Council for Research on International Economic Relations (ICRIER), 2017)
Bihar's agricultural development in the latest 10 years between 2005-06 and 2014-15, presents a mixed picture. Agriculture growth was around 4.7 per cent, which was above the national average of 3.6 per cent and in the latest five years, its performance was even more commendable, with an average annual growth rate of 7.1 per cent. However, agriculture productivity of two of its major crops, rice and wheat, is lower than the national average, despite the relatively high private investment in yield augmenting inputs such as fertilisers, certified seeds, tube wells and farm machines. Bihar's agriculture has diversified impressively through dairy development although productivity in milk production is lagging behind other major milk producing states, but poultry development has not taken off. In this paper, we study the composition, sources and drivers of agricultural growth in Bihar with a view to identifying the factors that explain the paradox of low agricultural productivity and high use of productivity augmenting inputs. The study finds that poor public investment in power, all-weather roads and marketing infrastructure, have constrained agriculture in Bihar. In particular, deficiencies in the power infrastructure have resulted in high dependency on diesel for pumping out groundwater for irrigation; this, along with soaring petroleum prices, has depressed returns from cultivation of crops. Further, the proportion of surfaced roads in the state is one of the lowest in the country and needs attention in order to link farmers to markets. Another major difficulty that farmers in Bihar face is the lack of marketing infrastructure, resulting in their inability to reap the price incentives given by the Government of India in the form of minimum support price. Livestock development has not achieved its potential because of strategic deficiencies. In dairy, productivity has remained low because germ plasm from superior breeds has not been used. In poultry, the culture of contract farming involving large integrator companies has not yet been adopted. In the light of these findings, the study makes five principal recommendations to stimulate agricultural growth and productivity in the state, viz., improve the quality and quantity of rural power supply by strengthening transmission and distribution and obtaining separation of feeders for irrigation, increase in the intensity of surfaced roads in rural areas, improve procurement and marketing infrastructure, improve health and reproduction management of dairy animals and obtain a quantum increase in poultry by employing the integrator model as has been done in states like Andhra Pradesh and Odisha.
Keywords: Q10; Q15; Q25; 330; Agricultural Growth; Irrigation; Power; Surfaced Roads; Marketing Infrastructure; Bihar